1999
DOI: 10.1021/je990056c
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Vitamin B6. 23. Interaction of Some Tertiary Ligating Amino Acids with the Binary Complexes of Ni(II) or Cu(II) and Pyridoxamine

Abstract: Binary and ternary complexes involved in the systems pyridoxamine (PM), glutamic acid (Glu), or aspartic acid (Asp) plus Ni(II) or Cu(II) were studied in solution at 0.15 M ionic strength and 25 °C by pH-metric, absorpiometric, and polarographic techniques. The differential pulse polarographic technique was used to study the reduction properties of these complexes. EPR was used to confirm the presence of binary and ternary complex species in the Cu(II) systems. The stoichiometry and formation constants of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Others [46] also suggested the presence of the Cu 2þ -hydroxo species shown in equation (8), further confirming our proposed speciation diagrams.…”
supporting
confidence: 87%
“…Others [46] also suggested the presence of the Cu 2þ -hydroxo species shown in equation (8), further confirming our proposed speciation diagrams.…”
supporting
confidence: 87%
“…A detailed literature survey indicated that the proposed binding mode of Asp to Cr 3+ is supported by the literature data [8,33,[35][36][37][38]. The bis-complex has the proposed structure shown in scheme 2 due to the following reasons: (1) The coordination sphere of the chromium ion is satisfied with six-donor atoms (MN 2 O 4 ), which is well documented in the literature [34][35][36], (2) the stability constants for both the simple one-to-one and the bis-complex have such high values indicating neither a mono-nor a bi-dentate nature; it must be tri-dentate [8,25,26], and (3) such structures have been seen with other metal ions, Cu 2+ and Co 3+ .…”
Section: Resultsmentioning
confidence: 66%
“…The bis-complex has the proposed structure shown in scheme 2 due to the following reasons: (1) The coordination sphere of the chromium ion is satisfied with six-donor atoms (MN 2 O 4 ), which is well documented in the literature [34][35][36], (2) the stability constants for both the simple one-to-one and the bis-complex have such high values indicating neither a mono-nor a bi-dentate nature; it must be tri-dentate [8,25,26], and (3) such structures have been seen with other metal ions, Cu 2+ and Co 3+ . Distribution diagrams clearly showed that the biscomplex is the dominant species at the physiological pH value.…”
Section: Resultsmentioning
confidence: 84%
“…A survey of the literature data revealed that most of the relevant studies provide the stability constants for only two Cu 2+ complexes with aspartic acid: CuAsp and Various protonated species (CuHAsp + , CuH 2 Asp 2+ , and CuH 2 Asp 2 have been detected in [1][2][3][4][5]; their stability constants are cited. Data on the heat effects of complexation in this system are scarce and contradictory.…”
mentioning
confidence: 99%
“…where Δ r H and Δ r H° are the enthalpy changes in reac tions (1) or (2) CuAsp r H Δ CuAsp r H Table 3. The calculated thermodynamic characteris tics of the complexation in the system Cu(II)-L aspartic acid at I = 0, 0.5, 0.75, and 1.0 and Т = 298.15 K are summarized in Table 3; for comparison, the corresponding data for nickel(II) complexes [20] are cited.…”
mentioning
confidence: 99%